Distal Extra-articular Tibia Fractures in Adults: A comparison of treatment outcomes with external fixators versus anatomical plates - محمد, محمد; معن سعد ,; غياث حلوم , (Latakia University Journal -Medical Sciences Series, 2023)
Objective: evaluate the functional and radiographic outcomes after distal tibia outcome parameters included occurrence of complications, radiographic analysis, evaluation of the American Orthopaedic Foot and Ankle Society (AOFAS) ankle score and measures of the ankle range of motion. Patients and methods: A retrospective-prospective study included 34 patients over 18 years old. The patients was divided ​​into 2 groups (external fixation and orif). AOFAS score was performed after one year. The duration of the research was two years, from January 2020 to January 2022. Results: there was no statistically difference between the two groups of overall results according to AOFAS score , and the results were excellent and good in the vast majority of patients. Excellent and good results were convergent in males and females. the results of type A1 group were better than the A2 and A3 groups classification. Healing was better in the younger group. Conclusion: ORIF with anatomical plates as early as possible, if the condition of the soft tissues allows it, as they provide a solid fixation and allow early mobilization of the ankle joint and a faster return to working life, with an emphasis on respecting the blood supply of the skin and fracture fragments, and it is preferable to keep the external fixator (AO) that crosses the ankle joint for cases that do not In which the soft tissue condition allows open reduction, or as the first stage of a two-stage treatment..